PENERAPAN METODE OUTING CLASS DALAM MEMBANGUN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA A.WAHID HASYIM TEBUIRENG JOMBANG - Nurrindah Ayu Puspita; Shobihus Surur (JURNAL ILMIAH NUSANTARA, 2025)
This study discusses the outing class method to improve students' learning motivation in Islamic Religious Education subjects at SMA A. Wahid Hasyim Tebuireng Jombang. This study uses a qualitative approach with descriptive and field types. Data were collected through observation, interviews, and documentation. Research informants included the principal, curriculum vice principal, Islamic Religious Education teachers, and students. Data analysis was carried out by triangulating sources to ensure the validity of the data. Based on the results of the study, it was found that: 1) The outing class method in Islamic Religious Education subjects at SMA A. Wahid Hasyim Tebuireng Jombang class X consists of three stages: planning (teachers prepare modules, select materials, determine locations, and ask permission), implementation (discussion and Q&A between groups), and evaluation (oral and written reflections and practice questions in the Islamic Religious Education and Character Building books for class X pages 142-145). 2) Students' learning motivation at SMA A. Wahid Hasyim Tebuireng Jombang increased, as evidenced by the enthusiasm for learning and students' positive responses to the outing class method. 3) The outing class method can make students more active because it creates an interesting learning atmosphere and direct experience that combines physical activity with conceptual understanding. This method also increases students' self-confidence, driven by the desire to succeed, the need to learn, and future hopes. Awards, interesting activities, and a supportive environment strengthen this process.